Evidence for Symplastic Phloem Unloading in Sink Leaves of Barley - Haupt, Sophie (American Society of Plant Physiologists, 2001)
The pathway of phloem unloading in sink barley (Hordeum vulgare) leaves was studied using a combination of electron microscopy, carboxyfluorescein transport, and systemic movement of barley stripe mosaic virus expressing the green fluorescent protein. Studies of plasmodesmatal frequencies between the phloem and mesophyll indicated a symplastic sieve element- (SE) unloading pathway involving thick-walled and thin-walled SEs. Phloem-translocated carboxyfluorescein was unloaded rapidly from major longitudinal veins and entered the mesophyll cells of sink leaves. Unloading was “patchy” along the length of a vein, indicating that sieve element unloading may be discontinuous along a single vascular bundle. This pattern was mirrored precisely by the unloading of barley stripe mosaic virus expressing the green fluorescent protein. Transverse veins were not utilized in the unloading process. The data collectively indicate a symplastic mechanism of SE unloading in the sink barley leaf.